THE USED GUNNY SACKS AND LEFTOVER LEATHER PRODUCTION IN THE DESIGN OF BOOTS FOR WOMEN WITH TIE DYE AND SMOCK TECHNIQUES: utilization of used materials and production waste - Efrita Ajeng Edya Arandita (Faculty Of Arts and Design Sebelas Maret University, 2023)
This design is based on the gunny sacks (jute) that accumulate in Keden market, Kec. Pedan, Kab. Klaten, Central Java, there are conditions that are still worth using again. Gunny sacks are still feasible to use as the main material and the rest of the leather production as a supporting material in the product design boots in this design. Tie dye and smock techniques are applied to the burlap sack as an element of decoration. Women's boots are currently a trend, synonymous with masculine style. The method applied in realizing the idea of designing these boots is the method of creating artwork by Gustami SP., namely in designing the work there are three steps that must be passed: the stage of exploration, design and visualization This design produces boots for women types of chelsea boots and wedges boots using the main material used gunny sacks given smock motifs and a combination of leather remaining production. Naphtol staining accompanied the visualization of the smock on this gunny sack.   Keyword : jute sacks, boots for woman, tie dye, smock technique, chemical dyes naphtol.